POTENSI EKSTRAK PEGAGAN (Centella Asiatica) DAN KUNYIT (Curcuma longa) UNTUK MENINGKATKAN AKTIVITAS ENZIM GLUTATION PEROKSIDASE (GSH Px) PADA JARINGAN HATI TIKUS - Tuti Aswani; Wasmen Manalu; Agik Suprayogi; Min Rahminiwati (Research Center for Biology-Indonesian Institute of Sciences, 2015)
This experiment was designed to study the effect of pegagan (Centella asiatica) and turmeric (Curcuma longa) extracts on the activities of glutathione peroxidase (GSH- Px) in liver of white Spraque Dawley rat aged 2 months old with average weight of 200 grams. Pegagan was extracted using infuse method, and turmeric was extracted using dekokta method. The activity of GSH-Px was measured using Flohe and Gunzler’s methods. Extract pegagan and turmeric were assumed to have both preventive and curative treatments. For the preventive treat- ment, extract pegagan and turmeric at concentrations of 22.05 mg/ml : 184.1 mg/ml could increased the activity of GSH-PX enzyme, i.e. 232.60 ± 21.40 mU / mgprotein. This was approximately 79% than the levels of GSH- Px enzyme in normal liver without paracetamol which was 190.78 ± 9.28 mU/mgprotein. For the curative treatment, extract pegagan and tumeric at concentration of 22.05 mg/ml : 184.1 mg/ml could improved GSH- Px enzyme activity (i.e. 239.01 ± 47.40 mU/ mgprotein). This figure was about 92% higher than the levels of GSH-Px enzyme in the liver normal without paracetamol which was 190.78 ± 9.28 mU/mg protein. Pegagan and turmeric extracts with a high concentration could increased the activity of GSH-Px enzyme, thus potential as curative treatment.